Cerebrospinal fluid penetration and combination therapy of entrectinib for disseminated ROS1/NTRK-fusion positive pediatric high-grade glioma - Mayr, Lisa; Guntner, Armin S.; Madlener, Sibylle; Schmook, Maria T.; Peyrl, Andreas; Azizi, Amedeo A.; Dieckmann, Karin; Reisinger, Dominik; Stepien, Natalia M.; Schramm, Kathrin; Laemmerer, Anna; Jones, David T. W.; et al. (International Journal of Person Centered Medicine, 2020)
Targeting oncogenic fusion-genes in pediatric high-grade gliomas (pHGG) with entrectinib has emerged as a highly promising therapeutic approach. Despite ongoing clinical studies, to date, no reports on the treatment of cerebrospinal fluid (CSF) disseminated fusion-positive pHGG exist. Moreover, clinically important information of combination with other treatment modalities such as intrathecal therapy, radiotherapy and other targeted agents is missing. We report on our clinical experience of entrectinib therapy in two CSF disseminated ROS1/NTRK-fusion-positive pHGG cases. Combination of entrectinib with radiotherapy or intrathecal chemotherapy appears to be safe and has the potential to act synergistically with entrectinib treatment. In addition, we demonstrate CSF penetrance of entrectinib for the first time in patient samples suggesting target engagement even upon CSF dissemination. Moreover, in vitro analyses of two novel cell models derived from one case with NTRK-fusion revealed that combination therapy with either a MEK (trametinib) or a CDK4/6 (abemaciclib) inhibitor synergistically enhances entrectinib anticancer effects. In summary, our comprehensive study, including clinical experience, CSF penetrance and in vitro data on entrectinib therapy of NTRK/ROS1-fusion-positive pHGG, provides essential clinical and preclinical insights into the multimodal treatment of these highly aggressive tumors. Our data suggest that combined inhibition of NTRK/ROS1 and other therapeutic vulnerabilities enhances the antitumor effect, which should be followed-up in further preclinical and clinical studies.